If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 9 = 6y + -2 Reorder the terms: 9 + 7y = 6y + -2 Reorder the terms: 9 + 7y = -2 + 6y Solving 9 + 7y = -2 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 9 + 7y + -6y = -2 + 6y + -6y Combine like terms: 7y + -6y = 1y 9 + 1y = -2 + 6y + -6y Combine like terms: 6y + -6y = 0 9 + 1y = -2 + 0 9 + 1y = -2 Add '-9' to each side of the equation. 9 + -9 + 1y = -2 + -9 Combine like terms: 9 + -9 = 0 0 + 1y = -2 + -9 1y = -2 + -9 Combine like terms: -2 + -9 = -11 1y = -11 Divide each side by '1'. y = -11 Simplifying y = -11
| 645-07-04-00-00_files/i0090000.jpg | | (83-x)=180 | | 3=x/3.3 | | (0,29x)/(0,4-0,4x^2,39) | | x/6=3/4 | | x^8+254x^4+1=0 | | (5x+11)=180 | | (M-9)+6=4(m-2)-2(m-6) | | 2x+13=-5x-7x | | 18a/6 | | (7+5i)+(5i)= | | (x-2x/100)*60/100*70/100=7203 | | (5x+11)=360 | | (-8i)-(3i)= | | 4d=1/3 | | x+(3x+15)=135 | | 256x^2=-176 | | Y+5-6y=17-2y | | 1.2c=0.6 | | (3i)-(I)= | | 3d+5d+9d-8= | | f(x)=6x^3+11x^2-10x | | (8j-9)=14 | | 6=3/5w | | 4(d+3)= | | 2w-3=2w | | a+5a+4b= | | 1.6x=2.5y+2 | | 7v/6=42 | | 7+9x=180 | | 9*x^2+3*x-2=0 | | 17+4x=180 |